Diversity and distribution of thermophilic microorganisms and their applications in biotechnology. (8th December 2021) - Arbab, Safia; Ullah, Hanif; Khan, Muhammad I. U.; Khattak, Muhammad N. K.; Zhang, Jiyu; Li, Ka; Hassan, Inam Ul
Abstract: Hot springs ecosystem is the most ancient continuously inhabited ecosystem on earth which harbors diverse thermophilic bacteria and archaea distributed worldwide. Life in extreme environments is very challenging so there is a great potential biological dark matter and their adaptation to harsh environments eventually producing thermostable enzymes which are very vital for the welfare of mankind. There is an enormous need for a new generation of stable enzymes that can endure harsh conditions in industrial processes and can either substitute or complement conventional chemical processes. Here, we review at the variety and distribution of thermophilic microbes, as well as the different thermostable enzymes that help them survive at high temperatures, such as proteases, amylases, lipases, cellulases, pullulanase, xylanases, and DNA polymerases, as well as their special properties, such as high‐temperature stability. We have documented the novel isolated thermophilic and hyperthermophilic microorganisms, as well as the discovery of their enzymes, demonstrating their immense potential in the scientific community and in industry.